Accounting Fundamentals and the Variation of Stock Price: Factoring in the Investment Scalability - Sumiyana Sumiyana; Zaki Baridwan; Slamet Sugiri; Jogiyanto Hartono (Gadjah Mada International Journal of Business, 2010)
This study develops a new return model with respect to accounting fundamentals. The new return model is based on Chen and Zhang (2007). This study takes into account theinvestment scalability information. Specifically, this study splitsthe scale of firm’s operations into short-run and long-runinvestment scalabilities. We document that five accounting fun-damentals explain the variation of annual stock return. Thefactors, comprised book value, earnings yield, short-run andlong-run investment scalabilities, and growth opportunities, co associate positively with stock price. The remaining factor,which is the pure interest rate, is negatively related to annualstock return. This study finds that inducing short-run and long-run investment scalabilities into the model could improve the degree of association. In other words, they have value rel-evance. Finally, this study suggests that basic trading strategieswill improve if investors revert to the accounting fundamentals.Keywords: accounting fundamentals; book value; earnings yield; growth opportunities; shortrun and longrun investment scalabilities; trading strategy;value relevance